Pelatihan Penyusunan Kurikulum Operasional Sekolah Berbasis Merdeka di TK Khalifah Cendekia Mandiri Kabupaten Maros - Riskal Fitri; Abrina Maulidnawati Jumrah (LP2M Universitas Muhammadiyah Enrekang, 2022)
Community Service Activities (PKM) carried out by the PKM FKIP team at the Islamic University of Makassar in the form of Training on the Preparation of an Independent Curriculum-Based School Operational Curriculum. With the problems faced as follows: a) The implementation of early childhood education in this unit still does not meet the expected quality standards. One of them is the limited learning media or educational game tools in institutions; b) The lack of creativity of PAUD educators in developing interesting APE for children, so that children quickly get bored with learning; c) The curriculum used in institutions still uses the K13 curriculum and the independent curriculum is still in the process of being drafted d) Lack of collaboration with parents of students in learning activities. With this activity, it is hoped that school principals can facilitate teachers to attend training, workshops, or seminars on learning activities in PAUD as a form of effort to increase teacher creativity in designing learning. The creativity of a teacher is needed in designing learning activities, because in every learning activity the teacher is the main supporter in achieving aspects of child development. With the existence of independent curriculum materials it can make it easier for teachers when designing activities. An independent curriculum can also be one of the driving factors for requiring teachers to be creative.